2020
DOI: 10.3390/met10060757
|View full text |Cite
|
Sign up to set email alerts
|

High Nb–TiAl Intermetallic Blades Fabricated by Isothermal Die Forging Process at Low Temperature

Abstract: In this study, the isothermal die forging process of high Nb–TiAl (Ti-44Al-8Nb-0.2W-0.2B-Y, at.%) alloy blades was simulated using the ABAQUS V6.11 software and the blades were fabricated successfully. The influence of a low forging temperature (lower than 1000 °C) and strain rate on the distributions of effective strain and stress were analyzed. The results indicate that the effective strain exhibits negative temperature sensitivity and positive strain rate sensitivity. The stress exponent (n = 3.02) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The turbine wheel in this product was cast TiAl alloy, which was manufactured by precision casting and joined to a low-alloy steel shaft to form the turbine rotor. Even in recent research on the practical application of TiAl alloys, small blades [2,3] and engine valves [4] manufactured by casting, isothermal forging, and extrusion are targeted, and there are no development examples of parts weighing 0.5 kg or more. The TiAl alloy is currently mostly used in the low-pressure turbine blades of jet engines [5] Parts manufactured by precision casting were initially used for practical applications; however, because the TiAl alloy is poorly castable, casting a near-net into a blade shape was difficult, with very large surplus materials required, leading to large amounts of machining that effectively negated the merits of precision casting.…”
Section: Introductionmentioning
confidence: 99%
“…The turbine wheel in this product was cast TiAl alloy, which was manufactured by precision casting and joined to a low-alloy steel shaft to form the turbine rotor. Even in recent research on the practical application of TiAl alloys, small blades [2,3] and engine valves [4] manufactured by casting, isothermal forging, and extrusion are targeted, and there are no development examples of parts weighing 0.5 kg or more. The TiAl alloy is currently mostly used in the low-pressure turbine blades of jet engines [5] Parts manufactured by precision casting were initially used for practical applications; however, because the TiAl alloy is poorly castable, casting a near-net into a blade shape was difficult, with very large surplus materials required, leading to large amounts of machining that effectively negated the merits of precision casting.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced under the terms of the CC BY 4.0 license. [ 134 ] Copyright 2020, Xiaopeng Wang, Wenchen Xu, Peng Xu, Haitao Zhou, Fantao Kong, and Yuyong Chen. Reproduced with permission.…”
Section: Introductionmentioning
confidence: 99%
“…Different modeling techniques are suitable for different length scales and hence to address different problems. Left‐to‐right: finite‐element method (FEM) using continuum mechanics showing strain distribution in a blade made of TiAl−Nb alloy, [ 134 ] example of mesoscale modeling of dendrite growth in a β‐solidifying TiAl alloy using phase‐field modeling, [ 135 ] nanoscale atomistic simulation of a room‐temperature tensile test of γ‐TiAl, and valence charge distribution of ( 0001 ) plane of α 2 ‐Ti 3 Al. Reproduced under the terms of the CC BY 4.0 license.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment includes an intentional δ-phase precipitation cycle as a preparation for the subsequent thermomechanical processing. It has been reported that DP718 can produce uniform fine grains [17][18][19][20][21][22][23][24]. Although DP718 is derived from a process known as "mini grain" mainly used in ingot-billet conversion [25][26][27], it also finds an opportunity as a possible industrial forging process.…”
Section: Introductionmentioning
confidence: 99%